Augmentation of ribs turbulators height on the hydrothermal performance of double pipe heat exchanger - Al-Kayiem, H.H. (Taylor's University, 2017)
Thermal performance of double pipe heat exchanger can be enhanced by imposed turbulence in the annular flow using artificial roughening. This paper presents experimental results on enhancing the heat transfer by artificial roughening using energy promoters installed on the inner surface of the cold flow annulus. An experimental test rig was fabricated having 2.0 m long annular flow test section with 76.2 mm and 34.2 mm outside and inside diameters, respectively. The energy promoters have ribs shape with rectangular cross section. Two cases of rib’s pitch to height ratios, equal to 10 and 15 and three height to hydraulic diameter, equal to 0.0595, 0.0-3, and 0.107 have been studied. The investigations were carried out at various flow rates within Reynolds number range of 2900 to 21000 in the cold annulus. For each roughening case, the thermal and hydraulic performances were evaluated by determining Stanton number and the associated pressure drop, respectively. The experimental results showed that enhancement in the heat transfer was combined with a penalty in the pressure drop due to the increase in the friction factor values. The combined hydrothermal enhancement results of the DPHE, in terms of the performance index, indicate that the small height ribs to hydraulic diameter of 0.0595, augmented higher than the large height ribs to hydraulic diameter of 0.107. Hence, it is recommended to use ribs installed on the inner surface of the annulus ribs to hydraulic diameter in the range of 0.06 ± 0.005. Also, it is recommended to investigate further parameters to explore further on the influencing of the ribs on the hydrothermal performance of the DPHE. © School of Engineering, Taylor’s University.